Diversity in Sirex noctilio, Amylostereum areolatum and Deladenus siricidicola populations in Australasia and its implications for biological control - Slippers, Bernard (University of Pretoria, 2024)
Thesis (PhD (Genetics))--University of Pretoria, 2024.